2013
DOI: 10.1021/es3051313
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Quantification of Mining-Related “Naphthenic Acids” in Groundwater near a Major Oil Sands Tailings Pond

Abstract: The high levels of acid extractable organics (AEOs) containing naphthenic acids (NAs) found in oil sands process-affected waters (OSPW) are a growing concern in monitoring studies of aquatic ecosystems in the Athabasca oil sands region. The complexity of these compounds has substantially hindered their accurate analysis and quantification. Using a recently developed technique which determines the intramolecular carbon isotope signature of AEOs generated by online pyrolysis (δ(13)Cpyr), natural abundance radioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 44 publications
(91 reference statements)
9
59
0
Order By: Relevance
“…There was similarity between the organic components detected in the groundwater samples and the OSPW samples from Company A. Similarities between groundwater and industrial samples are in line with recent findings by Ahad et al [53], Frank et al [37], and Barrow et al [54]. This demonstrates a degree of overlap and potential for future environmental screening, especially if included in a multilevel approach that integrates geochemistry and other factors [37].…”
Section: Percentage Of Total Intensitysupporting
confidence: 86%
“…There was similarity between the organic components detected in the groundwater samples and the OSPW samples from Company A. Similarities between groundwater and industrial samples are in line with recent findings by Ahad et al [53], Frank et al [37], and Barrow et al [54]. This demonstrates a degree of overlap and potential for future environmental screening, especially if included in a multilevel approach that integrates geochemistry and other factors [37].…”
Section: Percentage Of Total Intensitysupporting
confidence: 86%
“…However, Janfada et al (2006) found preferential sorption of the individual NAs in soil, which could be important from a toxicity standpoint because different NA species have varying degrees of toxicity. Ahad et al (2013) highlighted the need for accurate characterization of the diversity of NA species to quantify potential seepage from tailings ponds. Savard et al (2012) developed a new method of carbon isotopic analysis of carboxyl groups to distinguish mining-related contaminants from natural background organic acids.…”
Section: Oil Sands Examplementioning
confidence: 99%
“…OSPW has demonstrated both acute and chronic toxicity to a number of species (Del Rio et al 2006;Wang et al 2013). The toxicity of OSPW is mainly due to the presence of a group of dissolved organic acids, known as Bnaphthenic acids^(NAs) which refer to a complex suite of alkyl-substituted acyclic and cycloaliphatic carboxylic acids (Clemente et al 2004;Ahad et al 2013). The Alberta government has posted a Bzero dischargep olicy for all OSPW (Government of Alberta 2010).…”
Section: Introductionmentioning
confidence: 99%